2020
DOI: 10.3390/agriculture10050174
|View full text |Cite
|
Sign up to set email alerts
|

Seeds of n-GM Soybean Varieties Cultivated in Poland and Their Processing Products as High-Protein Feeds in Cattle Nutrition

Abstract: Soybean (Glycine max (L.) Merr) is a source of high-quality edible protein and oil for humans, but also a high-quality feed in livestock feeding. In Poland, imported genetically modified soybean meal covers 65%, and leguminous seeds that are cultivated locally cover 11% of the protein requirement in livestock nutrition. The implementation of the Polish national program and the European strategy supporting the growth of the leguminous area resulted in adaptation to local agro-climatic conditions of 36 varieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The content of anti-nutrients in soybean products depends on the soybean cultivar and refining procedures [6,38,[40][41][42]. As regards trypsin inhibitors, it was demonstrated that the amount of these compounds is reduced to the greatest extent by heating [11,20,38,39]. The amount of trypsin inhibitors determined in soybean meal and in extruded full-fat soybean in our own studies corroborated the results of Milczarek et al [6].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The content of anti-nutrients in soybean products depends on the soybean cultivar and refining procedures [6,38,[40][41][42]. As regards trypsin inhibitors, it was demonstrated that the amount of these compounds is reduced to the greatest extent by heating [11,20,38,39]. The amount of trypsin inhibitors determined in soybean meal and in extruded full-fat soybean in our own studies corroborated the results of Milczarek et al [6].…”
Section: Discussionsupporting
confidence: 84%
“…Świ ątkiewicz et al [38] showed a similar amount (216 g•kg −1 ) of fat in extruded fullfat soybean but a higher amount (88 g•kg −1 ) in soybean expeller cake. According to Niwi ńska et al [39], the protein product derived from full-fat non-GM soybean seeds subject to pressure-thermal processing contains a lot of protein and fat as the source of energy and a low amount of anti-nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Individual farms are increasingly interested in purchasing the equipment which will help them to use soybean seeds as a high-protein feed (oral information from manufacturers of equipment for processing small amounts of seeds). Therefore, farmers should be encouraged to use small-scale seed processing equipment, e.g., toasters to make products of an increased protein nutritional value to feed cattle, extruders to make full-fat products of an increased protein and energy nutritional value by means of extrusion or skimmed extrusion products of an increased protein nutritional value, as well as screw presses to make high-quality press cakes [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, it requires substantially more water than cereal crops for successful production. Soybean seeds are widely used in the food industry as a rich source of high-quality protein and edible oil (Niwi nska et al 2020). Soybean is grown in tropical, subtropical and temperate regions.…”
Section: Introductionmentioning
confidence: 99%